Metal rolling - Asymmetrical rolling process. Issue 1 (January 2016) - Alexa, V; Raţiu, S; Kiss, I
Abstract: The development of theory and practice related to the asymmetric longitudinal rolling process is based on the general theory of metalworking by pressure and symmetric rolling theory, to which a large number of scientists brought their contribution. The rolling of metal materials was a serious problem throughout history, either economically or technically, because the plating technologies enabled the consumption of raw materials (scarce and expensive) to be reduced, while improving the mechanical properties. Knowing the force parameters related to asymmetric rolling leads to the optimization of energy and raw material consumption. This paper presents data on symmetric rolling process, in order to comparatively highlight the particularities of the asymmetric process.